Impact of Fermented Wheat Bran Dietary Fiber Addition on Dough Rheological Properties and Noodle Quality - Fan, Ling; Li, Li; Xu, Anmin; Huang, Jihong; Ma, Sen (Frontiers in Nutrition, 2022)
The study aimed to evaluate the effect of fermented wheat bran dietary fiber (FWBDF) on the rheological properties of the dough and quality of noodles and to compare this with that of the unfermented wheat bran dietary fiber (UWBDF). Wheat bran dietary fiber (WBDF) was fermented by Auricularia polytricha. The results showed that adding UWBDF/FWBDF increased the G' and G'' of the dough, converted α-helix and β-turn into β-sheet and random coil, respectively, inhibited water flow, increased cooking loss, and decreased the maximum resistance in the noodles. The formed gluten network was speculated to have a more random and rigid structure, resulting in the deterioration of the quality of noodles. Furthermore, the number of α-helix and A22 increased but the number of β-sheet and cooking loss decreased in the FWBDF group compared with the UWBDF group. FWBDF (≤4%) improved the hardness of noodles, while UWBDF decreased it. These changes indicated that fermentation could reduce the destructive effects of WBDF on the quality of noodles, providing a new perspective on balancing dietary fiber-rich and high-quality foods.